(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2011)
Due to the rigidities of the Spanish electoral law, of the 350 deputies who make up the Congress, only 248 are distributed according to the population of each province. Since the first allocation of seats, made in 1977 for the elections of that year, so for those of 2008, 40 MP have changed their constituency. 29 provinces were affected, more than the half. Through these changes we can get an idea of population movements and, therefore, economic development: the north and the Bay of Biscay are losing wealth to the benefit of the center and the Mediterranean.